DESAIN DAN ANALISIS PROSES MANUFAKTUR MESIN PENGIRIS SAYURAN SKALA INDUSTRI RUMAH TANGGA - Muhammad Rohim (2022)
The development of agribusiness sector in Indonesia has recently become populer among the Indonesia people and offers good business prospects. One of problems in small and medium insustries is the process of slicing raw materials witch still use the manual method with simple equipment using a knife for the slicing process. It is necessary to design and analyze the manufacturing process of household industrial scale vagetable slicing machine that can be operated easily and affordably. This is necessary to support the productivity of slicing vegetable for small and medium sixed industrial business sector (such warteg, catering, etc.). The result of the semi-otomatic vegetable slicing machine performance test conducted with four types of vegetable (namely onions, shallots, carrots, and cabbage.) were machines with a capacity of 24 kg/hour with slices ranging from 1,9mm - 2,9mm, the efficiency value was obtained assembly by 27,72%, and the dimensions of the vegetable slicing machine reach 300mm x 200mm x 490mm.